We are given the equations below.
9 8 7 6 5 4 3 2 1 9 8 7 6 5 4 3 2 1 9 8 7 6 5 4 3 2 1 9 8 7 6 5 4 3 2 1 9 8 7 6 5 4 3 2 1 9 8 7 6 5 4 3 2 1 9 8 7 6 5 4 3 2 1 × × × × × × × 9 1 8 2 7 3 6 4 5 5 4 6 3 = = = = = = = 0 8 8 8 8 8 8 8 8 8 9 1 7 7 7 7 7 7 7 7 7 8 2 6 6 6 6 6 6 6 6 6 7 3 5 5 5 5 5 5 5 5 5 6 4 4 4 4 4 4 4 4 4 4 5 5 3 3 3 3 3 3 3 3 3 4 6 2 2 2 2 2 2 2 2 2 3
What is the value of 9 8 7 6 5 4 3 2 1 × 7 2 ?
Note : Can you explain what is happening?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Yes, that is the pattern. Now, why is it happening? Note that the pattern breaks when we try and multiply by 90.
Log in to reply
Thanks for explaining it :)
The pattern "breaks" when we multiply by 9 × 1 0 where n = 1 0 gives us b = − 1 . If we substituted that into the final formula and did the "negative carry over", we will arrive at the value of 88888888890.
Problem Loading...
Note Loading...
Set Loading...
We note that the pattern is 9 8 7 6 5 4 3 2 1 × 9 n = a 9 b ’s b b b b b b b b b c , where a = n − 1 , b = 9 − n and c = 1 0 − n .
Therefore, for n = 8 , we have 7 1 1 1 1 1 1 1 1 1 2 .
For what is happening:
For positive integer n < 1 0 , the general equation is as follows:
9 8 7 6 5 4 3 2 1 × 9 n = 8 8 8 8 8 8 8 8 8 9 n = 8 8 8 8 8 8 8 8 8 8 n + n = 8 n ( 1 1 1 1 1 1 1 1 1 1 ) + n = ( 9 − 1 ) ( 1 1 1 1 1 1 1 1 1 1 ) n + n = 9 9 9 9 9 9 9 9 9 9 n − 1 1 1 1 1 1 1 1 1 1 n + n = 1 0 0 0 0 0 0 0 0 0 0 n − n − 1 1 1 1 1 1 1 1 1 1 n + n = 1 0 0 0 0 0 0 0 0 0 0 n − 1 1 1 1 1 1 1 1 1 1 n = n 0 0 0 0 0 0 0 0 0 0 − n n n n n n n n n n = a b b b b b b b b b c where a = n − 1 , b = 9 − n , c = 1 0 − n